2016
DOI: 10.1016/j.bodyim.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Stress exposure and generation: A conjoint longitudinal model of body dysmorphic symptoms, peer acceptance, popularity, and victimization

Abstract: This study examined the bidirectional (conjoint) longitudinal pathways linking adolescents' body dysmorphic disorder (BDD) symptoms with self- and peer-reported social functioning. Participants were 367 Australian students (45.5% boys, mean age=12.01 years) who participated in two waves of a longitudinal study with a 12-month lag between assessments. Participants self-reported their symptoms characteristic of BDD, and perception of peer acceptance. Classmates reported who was popular and victimized in their gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
2
12
0
4
Order By: Relevance
“…Furthermore, those children with BDD symptoms reported more negative perceptions of peer acceptance over time than their non-BDD counterparts. This supports a possible bi-directional social stress model, because it suggest that as a result of early teasing, individuals with BDD may distort objectively innocuous social situations, thereby self-perpetuating social difficulties over time [23].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, those children with BDD symptoms reported more negative perceptions of peer acceptance over time than their non-BDD counterparts. This supports a possible bi-directional social stress model, because it suggest that as a result of early teasing, individuals with BDD may distort objectively innocuous social situations, thereby self-perpetuating social difficulties over time [23].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
“…Of note, one recent study investigated self and peer reports of teasing and victimization in a childhood sample. [23]. Results indicated that greater peer victimization posed a risk for the escalation of symptoms congruent with BDD in the following year.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…At less clinically elevated levels, observer-reported attractiveness in early to middle adolescence has been found to show a weak negative association ( r = –.23) with body dissatisfaction, but this association became nonsignificant in late adolescence (Rosenblum & Lewis, 1999). A recent study of early adolescents found peer-rated attractiveness was not associated with concerns about appearance-based rejection by peers (Webb, Zimmer-Gembeck, & Mastro, 2016). In contrast, some studies have demonstrated positive associations between body size and appearance concerns among adolescents (Paxton, Eisenberg, & Neumark-Sztainer, 2006; Webb et al, 2015), including a study that found BMI to be significantly higher among a group of adolescents with a high level of BDD symptoms, compared to their healthier peers (Mastro et al, 2016).…”
Section: Predictors Of Growth In Appearance Anxietymentioning
confidence: 99%
“… 26 Several recent studies have shown associations between self-reported appearance-related teasing and BDD symptoms in analogue samples 27 28 and clinical samples, 29 particularly when the teasing is by members of the opposite sex. 27 In one of the only longitudinal studies of environmental risk factors in BDD, peer victimisation in school students (as reported by the peer group) was prospectively associated with the development of BDD symptoms 12 months later, 30 in line with suggestions that experiences of bullying may play a causal role in BDD. Although further research is clearly needed, understanding the role of environmental risk factors could have important implications for the prevention and early intervention in BDD.…”
Section: What Causes Bdd?mentioning
confidence: 55%